High-strength acid-resistant and temperature-resistant brick and preparation method thereof

CN122916637APending Publication Date: 2026-10-16JIANGXI NENGQIANG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611216362.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

湿法成型坯体含水率高,烘干周期长,极易出现开裂、变形、孔隙率偏高的问题,导致成品砖体致密性不足,抗压、抗折强度较低,长期高温酸碱环境下易出现渗蚀、剥落、破损

Benefits of technology

本申请通过将氧化钇与氧化铈复配形成晶相稳定剂,并制备耐酸无机改性液,结合负压雾化浸渍工艺完成对熔融石英粉体包覆改性,同时将十三氟辛基三乙氧基硅烷与甲基丙烯酰氧基丙基三甲氧基硅烷复配形成双功能偶联剂,用于纳米二氧化硅功能溶胶,并配合分段梯度干燥及梯度升温烧结一体化工艺,实现砖体的晶相稳定、界面结构强化与整体致密度提升,有效解决了传统耐酸耐温砖高温晶相畸变、界面结合松散、耐腐性单一、高温强度衰减快等缺陷,显著优化产品综合服役性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the technical field of industrial ceramic materials, and particularly discloses a high-strength acid-resistant and temperature-resistant brick and a preparation method thereof. The high-strength acid-resistant and temperature-resistant brick comprises the following raw materials: modified fused quartz powder, high bauxite clinker, calcined kaolin, active alumina powder, zirconium powder, glauconite, nano silicon dioxide functional sol and hydrophobic auxiliary agent. The preparation method of the high-strength acid-resistant and temperature-resistant brick comprises the following steps: (1) preparing dry powder mixture; (2) preparing dry green body; (3) preparing brick body green body; (4) sequentially performing segmented gradient drying and gradient temperature rising sintering on the brick body green body, and then cooling after sintering is completed, and the high-strength acid-resistant and temperature-resistant brick is obtained through furnace cooling. The high-strength acid-resistant and temperature-resistant brick has excellent mechanical strength, acid corrosion resistance and high and low temperature cold and hot impact performance, low high-pressure pressure attenuation rate and small thermal conductivity, and solves the defects of poor thermal stability, easy cracking, weak corrosion resistance and fast high-pressure performance attenuation of traditional acid-resistant bricks.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of industrial ceramic materials, more particularly, it relates to a high-strength acid-resistant and temperature-resistant brick and a preparation method thereof. BACKGROUND

[0002] The acid-resistant and temperature-resistant brick is a core anticorrosive refractory lining material for extreme working conditions such as chemical industry, smelting, power, and environmental protection desulfurization, and is widely used for the inner lining protection of acid washing tanks, reaction towers, high-temperature flues, and waste liquid incineration equipment, and is long-term exposed to complex working conditions such as high temperature, strong acid and alkali corrosion, cold and hot alternating impact, and high pressure extrusion, and has strict requirements on the structural strength, temperature resistance, acid corrosion resistance, and thermal shock resistance of the brick body.

[0003] At present, the mainstream acid-resistant and temperature-resistant bricks on the market are mostly prepared by using a wet forming process, which needs to add a large amount of water and a binder for wet material mixing and extrusion forming, and has many inherent defects. The wet-formed green body has a high water content, a long drying cycle, and is prone to cracking, deformation, and high porosity, which leads to insufficient density of the finished brick body, low compressive and bending strength, and easy corrosion, peeling, and damage in a long-term high-temperature acid and alkali environment. At the same time, the wet forming process has high energy consumption, low production efficiency, and large wastewater discharge, which does not meet the green production requirements. In addition, the acid-resistant and temperature-resistant bricks prepared by using the existing dry forming process have poor high-temperature thermal stability and weak resistance to sudden temperature changes, and the conventional products can only withstand temperature difference impact below 100 DEG C, are prone to cracking and damage under a temperature difference of 200 DEG C or above, and have obvious attenuation of acid resistance and high-temperature strength, and a short service life, which cannot meet the needs of high-end industrial extreme working conditions. The formula of a few dry-formed acid-resistant bricks in the prior art is not reasonable, the forming pressure parameters are not accurate, the particle combination in the brick body is poor, and the strength is uneven and the high-temperature creep resistance is insufficient, which cannot meet the multiple performances of high strength, high acid resistance, and high temperature resistance. Therefore, it is a technical problem to be solved in the current field to develop an acid-resistant and temperature-resistant brick and a preparation method thereof which are suitable for the dry forming process, have super high strength, excellent acid resistance, temperature resistance, and thermal shock resistance. SUMMARY

[0004] In order to solve the technical problems mentioned in the background, the present application provides a high-strength acid-resistant and temperature-resistant brick and a preparation method thereof.

[0005] In a first aspect, the present application provides a high-strength acid-resistant and temperature-resistant brick, which adopts the following technical scheme: A high-strength acid-resistant and temperature-resistant brick comprises the following raw materials by weight: modified fused quartz powder 40-55 parts, bauxite clinker 20-30 parts, calcined kaolin 10-20 parts, active alumina powder 8-15 parts, zirconium powder 5-8 parts, glauconite 8-10 parts, nano-silicon dioxide functional sol 5-8 parts, and hydrophobic auxiliary agent 0.5-1.5 parts.

[0006] Preferably, the preparation method of the modified fused quartz powder comprises the following preparation steps: The acid-resistant inorganic modification liquid is used to coat the fused quartz powder by a negative pressure atomization immersion process to obtain a modified powder; the modified powder is dried at low temperature, calcined at high temperature, crushed and sieved to obtain the modified fused quartz powder.

[0007] Preferably, the acid-resistant inorganic modification liquid is composed of zirconium tetrachloride, crystal phase stabilizer and anhydrous ethanol with a mass ratio of 10-12:0.3-0.8:100.

[0008] Preferably, the crystal phase stabilizer is composed of yttrium oxide and cerium oxide with a mass ratio of 5-8:1-2.

[0009] Preferably, the mass ratio of the acid-resistant inorganic modification liquid to the fused quartz powder is 0.2-0.4:1.

[0010] Preferably, in the negative pressure atomization immersion process, the negative pressure is-0.03MPa to-0.05MPa, and the atomization spraying rate is 5-8mL / min.

[0011] Preferably, the low-temperature drying temperature is 80-100℃, and the drying time is 1.5-2.5h.

[0012] Preferably, the high-temperature calcination specifically comprises the following steps: increasing the temperature to 1150-1250℃ at a temperature increasing rate of 4-6℃ / min, calcining for 2-3h, then slowly cooling to 500℃ at a temperature decreasing rate of 2-3℃ / min, and naturally cooling to room temperature.

[0013] Preferably, the preparation method of the nano-silicon dioxide functional sol comprises the following preparation steps: The tetraethyl orthosilicate is mixed with anhydrous ethanol, stirred uniformly, the alkaline catalytic liquid is added dropwise, and the hydrolysis reaction is carried out at constant temperature for 3-5h to obtain a nano-silicon dioxide sol; the bifunctional organosilane coupling agent is added dropwise into the nano-silicon dioxide sol, constant temperature stirring is carried out for 3-5h, impurities are removed after cooling and filtering to obtain the nano-silicon dioxide functional sol.

[0014] Preferably, the alkaline catalytic liquid is composed of ammonia water, anhydrous ethanol and deionized water with a mass ratio of 12-18:25-35:50-60.

[0015] Preferably, the mass concentration of the ammonia water is 25-28%.

[0016] Preferably, the mass ratio of the tetraethyl orthosilicate, anhydrous ethanol and alkaline catalytic liquid is 1-2:2.5-4:0.6-1.2.

[0017] Preferably, the alkaline catalytic liquid is added dropwise for 30-50min.

[0018] Preferably, the mass ratio of the nanometer silica sol and the bifunctional organosilane coupling agent is 100:4-7.

[0019] Preferably, the dropping duration of the bifunctional organosilane coupling agent is 40-60 min.

[0020] Preferably, the bifunctional organosilane coupling agent is composed of tridecafluoro octyl triethoxysilane and methacryloxy propyl trimethoxysilane with a mass ratio of 8-12:3-5.

[0021] Preferably, the hydrophobic auxiliary agent is stearic acid and / or polyethylene wax.

[0022] Preferably, the SiO2 of the fused quartz powder is ≥99.5%, and the particle size is 200-300 mesh.

[0023] Preferably, the AI2O3 of the bauxite clinker is ≥75%, and the particle size is 200-300 mesh.

[0024] Preferably, the AI2O3 of the calcined kaolin is ≥50%, and the particle size is 200-300 mesh.

[0025] Preferably, the AI2O3 of the active alumina powder is ≥99.5%, and the particle size is 200-300 mesh.

[0026] Preferably, the ZrO2 of the zircon powder is ≥65%, and the particle size is 200-300 mesh.

[0027] Preferably, the particle size of the pyrophyllite is 200-300 mesh.

[0028] Preferably, the particle size of the nanometer silica is ≤50 nm.

[0029] In a second aspect, the application further provides a preparation method of the high-strength acid-resistant and temperature-resistant brick. The preparation method of the high-strength acid-resistant and temperature-resistant brick comprises the following preparation steps: (1) Put the modified fused quartz powder, bauxite clinker, calcined kaolin, active alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, dry mix and stir for 15-25 min, mix uniformly, and obtain a dry powder mixture; (2) Add the hydrophobic auxiliary agent and nanometer silica functional sol to the dry powder mixture, continue to mix and stir for 10-15 min, and obtain a dry green body; (3) Press the dry green body into a brick body green body by isostatic pressing process; (4) sequentially segmentally gradient drying and gradient temperature rising sintering are carried out on the green brick body, after sintering, cooling, cooling in the furnace, polishing, sorting and testing, the high-strength acid-resistant and temperature-resistant brick is obtained.

[0030] Preferably, the forming pressure in the step (3) is 25-35 MPa, and the pressure maintaining time is 20-30 s.

[0031] Preferably, the segmental gradient drying in the step (4) is specifically: first, pre-drying at 60-70 DEG C for 1-2 h, then, temperature rising to 100-120 DEG C for constant temperature drying for 4-6 h.

[0032] Preferably, the gradient temperature rising sintering process in the step (4) is specifically: temperature rising from room temperature to 600-650 DEG C at a temperature rising rate of 3-5 DEG C / min, maintaining for 1-2 h, then, temperature rising to 1280-1350 DEG C at a temperature rising rate of 5-8 DEG C / min, constant temperature sintering for 4-6 h.

[0033] Preferably, the cooling rate in the step (4) is 2-4 DEG C / min.

[0034] In summary, the present application has the following beneficial effects: The present application forms a crystal phase stabilizer by compounding yttrium oxide and cerium oxide, and prepares an acid-resistant inorganic modified liquid, completes the coating modification of the fused quartz powder by combining with the negative pressure atomization impregnation process, simultaneously forms a bifunctional coupling agent by compounding tridecafluorooctyltriethoxysilane and methacryloyloxypropyltrimethoxysilane, and uses the bifunctional coupling agent for nano-silicon dioxide functional sol, and cooperates with the segmental gradient drying and gradient temperature rising sintering integrated process, realizes the crystal phase stability, interface structure strengthening and overall density improvement of the brick body, effectively solves the defects of high-temperature crystal phase distortion, loose interface combination, single corrosion resistance and rapid high-temperature strength attenuation of the traditional acid-resistant and temperature-resistant brick, and significantly optimizes the comprehensive service performance of the product.

[0035] The crystal phase stabilizer in the present application can fully play the synergistic effect of rare earth ions, the yttrium oxide can stabilize the high-temperature cristobalite crystal phase of the fused quartz, inhibit the crystal phase transformation, volume expansion and micro-cracking problems in the high-temperature calcination and subsequent sintering process, and consolidate the high-temperature structure stability of the powder; the cerium oxide can refine the crystal grains, activate the powder interface, improve the coating uniformity of the acid-resistant modified liquid, promote the uniform solid solution of zirconium element, form a continuous and dense zirconium-based acid-resistant protective layer on the surface of the powder, and endow the modified fused quartz powder with excellent temperature resistance and acid resistance, and improve the interface adaptability of the modified fused quartz powder with high alumina bauxite, calcined kaolin and other raw materials.

[0036] The bifunctional compounded silane coupling agent formed in the application has the dual advantages of hydrophobic corrosion resistance and interface bonding. The tridecafluoro-octyl triethoxysilane can construct a hydrophobic corrosion-resistant film layer on the surface of the silica sol, effectively blocking the penetration and corrosion of acid and alkali medium. The methacryloyloxypropyl trimethoxysilane can strengthen the interface bonding of the sol and inorganic powder through chemical bonding, eliminating the defects of interface delamination and loose bonding. The two components are complementary to each other, breaking through the limitations of single coupling agent function, and making the nano-silica functional sol have the properties of filling densification, interface reinforcement and long-term corrosion-resistant and permeation-resistant performance.

[0037] In the application, under the synergistic effect of the double modification system and the gradient sintering process, the overall density and mechanical strength of the brick body are significantly improved. The stable crystal phase structure, high-strength interface bonding and internal and external synergistic hydrophobic corrosion-resistant protection system can effectively reduce the thermal expansion coefficient of the brick body and inhibit high-temperature creep, and isolate the acid and alkali medium from eroding the matrix along the pores. The finally obtained acid-resistant and temperature-resistant brick has the advantages of high strength, high stability and long-term acid and alkali corrosion resistance, and can adapt to complex working conditions of industrial high-temperature corrosion. DETAILED DESCRIPTION

[0038] The application will be further described in detail below in combination with examples.

[0039] The stearic acid used in the examples and comparative examples of the application was purchased from Shandong Shengze Chemical Co., Ltd.; the polyethylene wax was purchased from Dongguan Qihuang Plastic Co., Ltd.; the tridecafluoro-octyl triethoxysilane was purchased from Wuhan Lingfan Technology Co., Ltd.; the methacryloyloxypropyl trimethoxysilane was purchased from Wuhan Zhongxiangyue New Material Technology Co., Ltd.; and the commercially available nano-silica sol was purchased from Qinghe County Ruijiang Metal Material Co., Ltd.

[0040] Examples 1-3 provide a high-strength acid-resistant and temperature-resistant brick and a preparation method thereof.

[0041] Example 1 A high-strength acid-resistant and temperature-resistant brick comprises the following raw materials by weight: modified fused quartz powder 40 parts, high alumina bauxite clinker 20 parts, calcined kaolin 10 parts, active alumina powder 8 parts, zirconium powder 5 parts, talc 8 parts, nano-silica functional sol 5 parts, and hydrophobic additive 0.5 part; wherein the hydrophobic additive is stearic acid.

[0042] The preparation method of the modified fused quartz powder comprises the following preparation steps: According to the mass ratio of acid-resistant inorganic modification liquid and fused quartz powder being 0.2:1, the fused quartz powder is uniformly coated and modified by using a negative pressure atomization immersion process; under the conditions of 20℃, negative pressure-0.03MPa, and atomization spraying rate 5mL / min, the acid-resistant inorganic modification liquid uniformly infiltrates the surface of the fused quartz powder by continuously closed atomization immersion for 20min, so that the modified powder with uniform coating is obtained; the modified powder is placed in a hot air drying oven and dried at 80℃ for 1.5h, and then the dried powder is placed in a high-temperature kiln and heated to 1150℃ at a heating rate of 4℃ / min, and then calcined at constant temperature for 2h; then, the temperature is slowly cooled to 500℃ at a rate of 2℃ / min, and then naturally cooled to room temperature; the cooled powder is crushed and passed through a 200-mesh standard sieve to obtain the modified fused quartz powder; wherein the acid-resistant inorganic modification liquid is composed of zirconium tetrachloride, crystal phase stabilizer and anhydrous ethanol with a mass ratio of 10:0.3:100; the crystal phase stabilizer is composed of yttrium oxide and cerium oxide with a mass ratio of 5:1.

[0043] The preparation method of the nano-silica functional sol comprises the following preparation steps: The mass ratio of tetraethyl orthosilicate, anhydrous ethanol and alkaline catalyst liquid is controlled to be 1:2.5:0.6, the tetraethyl orthosilicate is mixed with the anhydrous ethanol, stirring is carried out at room temperature and a stirring speed of 200 rpm for 10 min until the system is completely mixed and uniform; then the alkaline catalyst liquid is uniformly added into the system at a dropping speed for 30 min; after the dropping is completed, the temperature of the system is controlled to be 45℃ and the stirring speed is controlled to be 200 rpm, and the hydrolysis reaction is carried out at constant temperature for 3h to obtain a nano-silica sol; the mass ratio of the nano-silica sol and the bifunctional organosilane coupling agent is controlled to be 100:4, the bifunctional organosilane coupling agent is uniformly added into the obtained nano-silica sol at a dropping speed for 40 min; after the dropping is completed, the temperature of the system is maintained to be 45℃ and the stirring speed is maintained to be 200 rpm, and the reaction is carried out at constant temperature for 3h; after the reaction is completed, the system is naturally cooled to room temperature, impurities are removed by filtering with a 200-mesh filter cloth to obtain the nano-silica functional sol; wherein the alkaline catalyst liquid is composed of ammonia water, anhydrous ethanol and deionized water with a mass ratio of 12:25:50, and the mass concentration of the ammonia water is 25%; the bifunctional organosilane coupling agent is composed of tridecafluorooctyltriethoxysilane and methacryloyloxypropyltrimethoxysilane with a mass ratio of 8:3.

[0044] A preparation method of a high-strength acid-resistant and temperature-resistant brick comprises the following preparation steps: (1) The modified fused quartz powder, bauxite clinker, calcined kaolin, active alumina powder, zircon powder and pyrophyllite are put into a high-speed dry powder mixer, dry mixing and stirring are carried out at a stirring speed of 800 rpm at room temperature for 15 min, and then the mixture is uniformly mixed to obtain a dry powder mixture; (2) adding hydrophobic aids and nano-silica functional sol to the dry powder mixture, and continuing to mix at a stirring speed of 800 rpm for 10 min at room temperature to obtain dry green body; (3) loading the dry green body into a mold, and pressing to form a brick body green body by isostatic pressing process, with a forming pressure of 25 MPa and a pressure maintaining time of 20 s; (4) performing segmented gradient drying on the brick body green body, first pre-drying at 60 ℃ for 1 h to remove free water on the surface of the green body, then heating to 100 ℃ for constant temperature drying for 4 h, after drying, performing gradient sintering by uniformly heating from room temperature to 600 ℃ at a heating rate of 3 ℃ / min, maintaining for 1 h, then continuously heating to 1280 ℃ at a heating rate of 5 ℃ / min, maintaining for 4 h, after sintering, cooling to 800 ℃ at a rate of 2 ℃ / min, and cooling to room temperature in the furnace, after taking out of the furnace, polishing, sorting and testing to obtain high-strength acid-resistant and temperature-resistant bricks.

[0045] Example 2 A high-strength acid-resistant and temperature-resistant brick comprises the following raw materials by weight: modified fused quartz powder 48 parts, bauxite clinker 25 parts, calcined kaolin 15 parts, active alumina powder 12 parts, zircon powder 7 parts, pyrophyllite 9 parts, nano-silica functional sol 7 parts, and hydrophobic aids 1 part; wherein the hydrophobic aids are polyethylene wax.

[0046] The preparation method of the modified fused quartz powder comprises the following preparation steps: The fused quartz powder is uniformly coated and modified by a negative pressure atomization immersion process according to a mass ratio of acid-resistant inorganic modification liquid to fused quartz powder of 0.3:1; under the conditions of 25 ℃, negative pressure of-0.04 MPa, and atomization spraying rate of 7 mL / min, the acid-resistant inorganic modification liquid is uniformly infiltrated into the surface of the fused quartz powder by continuous closed atomization immersion for 30 min, to obtain uniformly coated modified powder; the modified powder is placed in a hot air drying oven for low-temperature drying at 90 ℃ for 2 h, and the dried powder is placed in a high-temperature kiln for gradient heating to 1200 ℃ at a heating rate of 5 ℃ / min, and constant temperature calcination for 2.5 h; then, the powder is slowly cooled to 500 ℃ at a rate of 2.5 ℃ / min, and naturally cooled to room temperature; the cooled powder is crushed to pass through a 250-mesh standard sieve to obtain the modified fused quartz powder; wherein the acid-resistant inorganic modification liquid is composed of zirconium tetrachloride, crystal phase stabilizer and anhydrous ethanol in a mass ratio of 11:0.5:100; the crystal phase stabilizer is composed of yttrium oxide and cerium oxide in a mass ratio of 7:1.5.

[0047] The preparation method of the nano-silica functional sol comprises the following preparation steps: The mass ratio of tetraethyl orthosilicate, anhydrous ethanol, and alkaline catalyst was controlled at 1.5:3:0.8. First, tetraethyl orthosilicate and anhydrous ethanol were mixed and stirred at room temperature and 300 rpm for 12 minutes until the system was completely homogeneous. Then, the alkaline catalyst was added dropwise to the system at a uniform rate over a period of 40 minutes. After the addition was complete, the system temperature was controlled at 50℃ and the stirring speed at 250 rpm, and the hydrolysis reaction was carried out at this constant temperature for 4 hours to obtain nano-silica sol. The mass ratio of nano-silica sol to bifunctional organosilane coupling agent was controlled at 100:6. The obtained nano-silica sol was then... A bifunctional organosilane coupling agent was added dropwise to the sol at a uniform rate over a period of 50 minutes. After the addition was complete, the system temperature was maintained at 50°C and the stirring speed at 250 rpm for 4 hours. After the reaction was completed, the sol was allowed to cool naturally to room temperature and filtered through a 200-mesh filter cloth to remove impurities, yielding a nano-silica functional sol. The alkaline catalyst consisted of ammonia, anhydrous ethanol, and deionized water in a mass ratio of 15:30:55, with an ammonia concentration of 27%. The bifunctional organosilane coupling agent consisted of tridecafluorooctyltriethoxysilane and methacryloxypropyltrimethoxysilane in a mass ratio of 10:4.

[0048] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 20 minutes at a stirring speed of 900 rpm until the mixture is uniform to obtain a dry powder mixture. (2) Add hydrophobic additives and nano-silica functional sol to the dry powder mixture, and continue mixing and stirring at room temperature for 13 minutes with a stirring speed of 900 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The pressing pressure is controlled at 30MPa and the pressure is held for 25s to obtain the brick blank. (4) The green bricks are dried in sections and gradients. First, they are pre-dried at 65℃ for 1.5h to remove free moisture from the surface of the bricks. Then, they are heated to 110℃ and dried at a constant temperature for 5h. After drying, they are sintered by gradient heating. The temperature is raised from room temperature to 625℃ at a rate of 4℃ / min and held for 1.5h. Then, the temperature is raised to 1320℃ at a rate of 7℃ / min and sintered at a constant temperature for 5h. After sintering, the temperature is lowered to 800℃ at a rate of 3℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, they are polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0049] Example 3 A high-strength, acid-resistant, and heat-resistant brick comprises the following raw materials in parts by weight: 55 parts modified fused silica powder, 30 parts high-alumina bauxite clinker, 20 parts calcined kaolin, 15 parts activated alumina powder, 8 parts zircon powder, 10 parts pyrophyllite, 8 parts nano-silica functional sol, and 1.5 parts hydrophobic additive; wherein the hydrophobic additive is composed of stearic acid and polyethylene wax in a mass ratio of 1:1.

[0050] The method for preparing modified fused silica powder includes the following preparation steps: The fused silica powder was uniformly coated and modified using a negative pressure atomization impregnation process with a mass ratio of acid-resistant inorganic modifying liquid to fused silica powder of 0.4:1. Under conditions of 30℃, negative pressure -0.05MPa, and atomization spray rate of 8mL / min, continuous closed atomization impregnation was performed for 40min to ensure uniform wetting of the fused silica powder surface by the acid-resistant inorganic modifying liquid, resulting in uniformly coated modified powder. The modified powder was then placed in a hot air drying oven and dried at 100℃ for 2.5h. The dried powder was placed in a high-temperature kiln and heated to 1250℃ at a rate of 6℃ / min, and calcined at a constant temperature for 3 hours. Then it was slowly cooled to 500℃ at a rate of 3℃ / min and allowed to cool naturally to room temperature. The cooled powder was then pulverized and passed through a 300-mesh standard sieve to obtain modified fused silica powder. The acid-resistant inorganic modification solution consisted of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 12:0.8:100. The crystal phase stabilizer consisted of yttrium oxide and cerium oxide in a mass ratio of 8:2.

[0051] The preparation method of the nano-silica functional sol includes the following preparation steps: The mass ratio of tetraethyl orthosilicate, anhydrous ethanol, and alkaline catalyst was controlled at 2:4:1.2. First, tetraethyl orthosilicate and anhydrous ethanol were mixed and stirred at room temperature and 400 rpm for 15 min until the system was completely homogeneous. Then, the alkaline catalyst was added dropwise to the system at a uniform rate over 50 min. After the addition was complete, the system temperature was controlled at 55℃ and the stirring speed at 300 rpm, and the hydrolysis reaction was carried out at this constant temperature for 5 h to obtain nano-silica sol. The mass ratio of nano-silica sol to bifunctional organosilane coupling agent was controlled at 100:7. The resulting nano-silica sol was then... A bifunctional organosilane coupling agent was added dropwise at a uniform rate over a period of 60 minutes. After the addition was complete, the system temperature was maintained at 55°C and the stirring speed at 300 rpm for 5 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and filtered through a 200-mesh filter cloth to remove impurities, yielding a nano-silica functional sol. The alkaline catalyst consisted of ammonia, anhydrous ethanol, and deionized water in a mass ratio of 18:35:60, with an ammonia concentration of 28%. The bifunctional organosilane coupling agent consisted of tridecafluorooctyltriethoxysilane and methacryloxypropyltrimethoxysilane in a mass ratio of 12:5.

[0052] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 25 minutes at a stirring speed of 1000 rpm until uniformly mixed to obtain a dry powder mixture. (2) Add hydrophobic additives and nano silica functional sol to the dry powder mixture, and continue mixing and stirring at room temperature for 15 minutes with a stirring speed of 1000 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The molding pressure is controlled at 35MPa and the pressure is held for 30s to obtain the brick blank. (4) The green bricks are dried in stages and gradients. First, they are pre-dried at 70℃ for 2 hours to remove free moisture from the surface of the bricks. Then, they are heated to 120℃ and dried at a constant temperature for 6 hours. After drying, they are sintered by gradient heating. The temperature is raised from room temperature to 650℃ at a rate of 5℃ / min and held for 2 hours. Then, the temperature is raised to 1350℃ at a rate of 8℃ / min and sintered at a constant temperature for 6 hours. After sintering, the temperature is lowered to 800℃ at a rate of 4℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, they are polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0053] Comparative Example 1 A high-strength, acid-resistant, and heat-resistant brick comprises the following raw materials in parts by weight: 40 parts modified fused silica powder, 20 parts high-alumina bauxite clinker, 10 parts calcined kaolin, 8 parts activated alumina powder, 5 parts zircon powder, 8 parts pyrophyllite, 5 parts nano-silica functional sol, and 0.5 parts hydrophobic additive; wherein the hydrophobic additive is stearic acid.

[0054] The method for preparing modified fused silica powder includes the following preparation steps: The fused silica powder was uniformly coated and modified using a negative pressure atomization impregnation process with a mass ratio of acid-resistant inorganic modification liquid to fused silica powder of 0.2:1. Under conditions of 20℃, negative pressure of -0.03MPa, and atomization spray rate of 5mL / min, continuous closed atomization impregnation was performed for 20min to ensure uniform wetting of the fused silica powder surface by the acid-resistant inorganic modification liquid, resulting in uniformly coated modified powder. The modified powder was then placed in a hot air drying oven and dried at a low temperature of 80℃. After 1.5 hours, the dried powder was placed in a high-temperature kiln and heated to 1150℃ at a rate of 4℃ / min, and calcined at a constant temperature for 2 hours. Then, it was slowly cooled to 500℃ at a rate of 2℃ / min and allowed to cool naturally to room temperature. The cooled powder was then pulverized and passed through a 200-mesh standard sieve to obtain modified fused silica powder. The acid-resistant inorganic modification solution consisted of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 10:0.3:100. The crystal phase stabilizer was yttrium oxide.

[0055] The preparation method of the nano-silica functional sol includes the following preparation steps: The mass ratio of tetraethyl orthosilicate, anhydrous ethanol, and alkaline catalyst was controlled at 1:2.5:0.6. First, tetraethyl orthosilicate and anhydrous ethanol were mixed and stirred at room temperature and 200 rpm for 10 min until the system was completely homogeneous. Then, the alkaline catalyst was added dropwise to the system at a uniform rate over 30 min. After the addition was complete, the system temperature was controlled at 45℃ and the stirring speed at 200 rpm, and the hydrolysis reaction was carried out at this constant temperature for 3 h to obtain nano-silica sol. The mass ratio of nano-silica sol to bifunctional organosilane coupling agent was controlled at 100:4. The resulting nano-silica... A bifunctional organosilane coupling agent was added dropwise to the sol at a uniform rate for 40 minutes. After the addition was complete, the system temperature was maintained at 45°C and the stirring speed at 200 rpm for 3 hours. After the reaction was completed, the mixture was naturally cooled to room temperature and filtered through a 200-mesh filter cloth to remove impurities, yielding a nano-silica functional sol. The alkaline catalyst consisted of ammonia, anhydrous ethanol, and deionized water in a mass ratio of 12:25:50, with an ammonia concentration of 25%. The bifunctional organosilane coupling agent consisted of tridecafluorooctyltriethoxysilane and methacryloxypropyltrimethoxysilane in a mass ratio of 8:3.

[0056] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 15 minutes at a stirring speed of 800 rpm until the mixture is uniform to obtain a dry powder mixture. (2) Add hydrophobic additives and nano silica functional sol to the dry powder mixture, and continue mixing and stirring at room temperature for 10 minutes with a stirring speed of 800 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The pressing pressure is controlled at 25MPa and the pressure is held for 20s to obtain the brick blank. (4) The green bricks are dried in sections and gradients. First, they are pre-dried at 60℃ for 1 hour to remove free moisture from the surface of the bricks. Then, they are heated to 100℃ and dried at a constant temperature for 4 hours. After drying, they are sintered by gradient heating. The temperature is raised from room temperature to 600℃ at a rate of 3℃ / min and held for 1 hour. Then, the temperature is raised to 1280℃ at a rate of 5℃ / min and sintered at a constant temperature for 4 hours. After sintering, the temperature is lowered to 800℃ at a rate of 2℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, they are polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0057] Comparative Example 2 A high-strength, acid-resistant, and heat-resistant brick comprises the following raw materials in parts by weight: 40 parts modified fused silica powder, 20 parts high-alumina bauxite clinker, 10 parts calcined kaolin, 8 parts activated alumina powder, 5 parts zircon powder, 8 parts pyrophyllite, 5 parts nano-silica functional sol, and 0.5 parts hydrophobic additive; wherein the hydrophobic additive is stearic acid.

[0058] The method for preparing modified fused silica powder includes the following preparation steps: The fused silica powder was uniformly coated and modified using a negative pressure atomization impregnation process with a mass ratio of acid-resistant inorganic modification liquid to fused silica powder of 0.2:1. Under conditions of 20℃, negative pressure of -0.03MPa, and atomization spray rate of 5mL / min, continuous closed atomization impregnation was performed for 20min to ensure uniform wetting of the fused silica powder surface by the acid-resistant inorganic modification liquid, resulting in uniformly coated modified powder. The modified powder was then placed in a hot air drying oven and dried at a low temperature of 80℃. After 1.5 hours, the dried powder was placed in a high-temperature kiln and heated to 1150℃ at a rate of 4℃ / min, and calcined at a constant temperature for 2 hours. Then, it was slowly cooled to 500℃ at a rate of 2℃ / min and allowed to cool naturally to room temperature. The cooled powder was then pulverized and passed through a 200-mesh standard sieve to obtain modified fused silica powder. The acid-resistant inorganic modification solution consisted of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 10:0.3:100. The crystal phase stabilizer was cerium oxide.

[0059] The preparation method of the nano-silica functional sol includes the following preparation steps: The mass ratio of tetraethyl orthosilicate, anhydrous ethanol, and alkaline catalyst was controlled at 1:2.5:0.6. First, tetraethyl orthosilicate and anhydrous ethanol were mixed and stirred at room temperature and 200 rpm for 10 min until the system was completely homogeneous. Then, the alkaline catalyst was added dropwise to the system at a uniform rate over 30 min. After the addition was complete, the system temperature was controlled at 45℃ and the stirring speed at 200 rpm, and the hydrolysis reaction was carried out at this constant temperature for 3 h to obtain nano-silica sol. The mass ratio of nano-silica sol to bifunctional organosilane coupling agent was controlled at 100:4. The resulting nano-silica... A bifunctional organosilane coupling agent was added dropwise to the sol at a uniform rate for 40 minutes. After the addition was complete, the system temperature was maintained at 45°C and the stirring speed at 200 rpm for 3 hours. After the reaction was completed, the mixture was naturally cooled to room temperature and filtered through a 200-mesh filter cloth to remove impurities, yielding a nano-silica functional sol. The alkaline catalyst consisted of ammonia, anhydrous ethanol, and deionized water in a mass ratio of 12:25:50, with an ammonia concentration of 25%. The bifunctional organosilane coupling agent consisted of tridecafluorooctyltriethoxysilane and methacryloxypropyltrimethoxysilane in a mass ratio of 8:3.

[0060] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 15 minutes at a stirring speed of 800 rpm until the mixture is uniform to obtain a dry powder mixture. (2) Add hydrophobic additives and nano silica functional sol to the dry powder mixture, and continue mixing and stirring at room temperature for 10 minutes with a stirring speed of 800 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The pressing pressure is controlled at 25MPa and the pressure is held for 20s to obtain the brick blank. (4) The green bricks are dried in sections and gradients. First, they are pre-dried at 60℃ for 1 hour to remove free moisture from the surface of the bricks. Then, they are heated to 100℃ and dried at a constant temperature for 4 hours. After drying, they are sintered by gradient heating. The temperature is raised from room temperature to 600℃ at a rate of 3℃ / min and held for 1 hour. Then, the temperature is raised to 1280℃ at a rate of 5℃ / min and sintered at a constant temperature for 4 hours. After sintering, the temperature is lowered to 800℃ at a rate of 2℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, they are polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0061] Comparative Example 3 A high-strength, acid-resistant, and heat-resistant brick comprises the following raw materials in parts by weight: 40 parts modified fused silica powder, 20 parts high-alumina bauxite clinker, 10 parts calcined kaolin, 8 parts activated alumina powder, 5 parts zircon powder, 8 parts pyrophyllite, 5 parts nano-silica functional sol, and 0.5 parts hydrophobic additive; wherein the hydrophobic additive is stearic acid.

[0062] The method for preparing modified fused silica powder includes the following preparation steps: The fused silica powder was uniformly coated and modified using a negative pressure atomization impregnation process with a mass ratio of acid-resistant inorganic modifying liquid to fused silica powder of 0.2:1. Under conditions of 20℃, negative pressure -0.03MPa, and atomization spray rate of 5mL / min, continuous closed atomization impregnation was performed for 20min to ensure uniform wetting of the fused silica powder surface by the acid-resistant inorganic modifying liquid, resulting in uniformly coated modified powder. The modified powder was then placed in a hot air drying oven and dried at 80℃ for 1.5h. The dried powder was placed in a high-temperature kiln and heated to 1150℃ at a rate of 4℃ / min, and calcined at a constant temperature for 2 hours. Then it was slowly cooled to 500℃ at a rate of 2℃ / min and allowed to cool naturally to room temperature. The cooled powder was then pulverized and passed through a 200-mesh standard sieve to obtain modified fused silica powder. The acid-resistant inorganic modification solution consisted of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 10:0.3:100. The crystal phase stabilizer consisted of yttrium oxide and cerium oxide in a mass ratio of 5:1.

[0063] The preparation method of the nano-silica functional sol includes the following preparation steps: The mass ratio of tetraethyl orthosilicate, anhydrous ethanol, and alkaline catalyst was controlled at 1:2.5:0.6. First, tetraethyl orthosilicate and anhydrous ethanol were mixed and stirred at room temperature and 200 rpm for 10 min until the system was completely homogeneous. Then, the alkaline catalyst was added dropwise to the system at a uniform rate over 30 min. After the addition was complete, the system temperature was controlled at 45℃ and the stirring speed at 200 rpm, and the hydrolysis reaction was carried out at this constant temperature for 3 h to obtain nano-silica sol. The mass ratio of nano-silica sol to bifunctional organosilane coupling agent was controlled at 10. A bifunctional organosilane coupling agent was added dropwise at a rate of 0:4 to the obtained nano-silica sol, with the addition time controlled at 40 min. After the addition was completed, the system temperature was maintained at 45℃ and the stirring speed at 200 rpm, and the reaction was carried out at a constant temperature for 3 h. After the reaction was completed, the mixture was naturally cooled to room temperature and filtered through a 200-mesh filter cloth to remove impurities, thus obtaining the nano-silica functional sol. The alkaline catalyst solution consisted of ammonia, anhydrous ethanol, and deionized water in a mass ratio of 12:25:50, with the mass concentration of ammonia being 25%. The bifunctional organosilane coupling agent was tridecafluorooctyltriethoxysilane.

[0064] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 15 minutes at a stirring speed of 800 rpm until the mixture is uniform to obtain a dry powder mixture. (2) Add hydrophobic additives and nano silica functional sol to the dry powder mixture, and continue mixing and stirring at room temperature for 10 minutes with a stirring speed of 800 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The pressing pressure is controlled at 25MPa and the pressure is held for 20s to obtain the brick blank. (4) The green brick body is subjected to a segmented gradient drying process: first, it is pre-dried at 60℃ for 1h to remove free moisture from the surface of the body; then, it is heated to 100℃ and dried at a constant temperature for 4h. After drying, it is subjected to gradient heating sintering. The temperature is raised from room temperature to 600℃ at a rate of 3℃ / min and held for 1h; then, it is heated to 1280℃ at a rate of 5℃ / min and sintered at a constant temperature for 4h. After sintering, it is cooled to 800℃ at a rate of 2℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, it is polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0065] Comparative Example 4 A high-strength, acid-resistant, and heat-resistant brick comprises the following raw materials in parts by weight: 40 parts modified fused silica powder, 20 parts high-alumina bauxite clinker, 10 parts calcined kaolin, 8 parts activated alumina powder, 5 parts zircon powder, 8 parts pyrophyllite, 5 parts nano-silica functional sol, and 0.5 parts hydrophobic additive; wherein the hydrophobic additive is stearic acid.

[0066] The method for preparing modified fused silica powder includes the following preparation steps: The fused silica powder was uniformly coated and modified using a negative pressure atomization impregnation process with a mass ratio of acid-resistant inorganic modifying liquid to fused silica powder of 0.2:1. Under conditions of 20℃, negative pressure -0.03MPa, and atomization spray rate of 5mL / min, continuous closed atomization impregnation was performed for 20min to ensure uniform wetting of the fused silica powder surface by the acid-resistant inorganic modifying liquid, resulting in uniformly coated modified powder. The modified powder was then placed in a hot air drying oven and dried at 80℃ for 1.5h. The dried powder was placed in a high-temperature kiln and heated to 1150℃ at a rate of 4℃ / min, and calcined at a constant temperature for 2 hours. Then it was slowly cooled to 500℃ at a rate of 2℃ / min and allowed to cool naturally to room temperature. The cooled powder was then pulverized and passed through a 200-mesh standard sieve to obtain modified fused silica powder. The acid-resistant inorganic modification solution consisted of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 10:0.3:100. The crystal phase stabilizer consisted of yttrium oxide and cerium oxide in a mass ratio of 5:1.

[0067] The preparation method of the nano-silica functional sol includes the following preparation steps: The mass ratio of tetraethyl orthosilicate, anhydrous ethanol, and alkaline catalyst was controlled at 1:2.5:0.6. First, tetraethyl orthosilicate and anhydrous ethanol were mixed and stirred at room temperature and 200 rpm for 10 min until the system was completely homogeneous. Then, the alkaline catalyst was added dropwise to the system at a uniform rate over 30 min. After the addition was complete, the system temperature was controlled at 45℃ and the stirring speed at 200 rpm, and the hydrolysis reaction was carried out at this constant temperature for 3 h to obtain nano-silica sol. The mass ratio of nano-silica sol to bifunctional organosilane coupling agent was controlled at 100:1. 4. Add the bifunctional organosilane coupling agent dropwise to the obtained nano-silica sol at a uniform rate for 40 min. After the addition is complete, maintain the system temperature at 45℃ and the stirring speed at 200 rpm for 3 h. After the reaction is complete, allow it to cool naturally to room temperature and filter it through a 200-mesh filter cloth to remove impurities, thus obtaining the nano-silica functional sol. The alkaline catalyst solution consists of ammonia, anhydrous ethanol and deionized water in a mass ratio of 12:25:50, with an ammonia concentration of 25%. The bifunctional organosilane coupling agent is methacryloyloxypropyltrimethoxysilane.

[0068] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 15 minutes at a stirring speed of 800 rpm until the mixture is uniform to obtain a dry powder mixture. (2) Add hydrophobic additives and nano silica functional sol to the dry powder mixture, and continue mixing and stirring at room temperature for 10 minutes with a stirring speed of 800 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The pressing pressure is controlled at 25MPa and the pressure is held for 20s to obtain the brick blank. (4) The green brick body is subjected to a segmented gradient drying process: first, it is pre-dried at 60℃ for 1h to remove free moisture from the surface of the body; then, it is heated to 100℃ and dried at a constant temperature for 4h. After drying, it is subjected to gradient heating sintering. The temperature is raised from room temperature to 600℃ at a rate of 3℃ / min and held for 1h; then, it is heated to 1280℃ at a rate of 5℃ / min and sintered at a constant temperature for 4h. After sintering, it is cooled to 800℃ at a rate of 2℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, it is polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0069] Comparative Example 5 A high-strength, acid-resistant, and heat-resistant brick comprises the following raw materials in parts by weight: 40 parts modified fused silica powder, 20 parts high-alumina bauxite clinker, 10 parts calcined kaolin, 8 parts activated alumina powder, 5 parts zircon powder, 8 parts pyrophyllite, 5 parts nano-silica functional sol, and 0.5 parts hydrophobic additive; wherein the hydrophobic additive is stearic acid.

[0070] The method for preparing modified fused silica powder includes the following preparation steps: The fused silica powder was uniformly coated and modified using a negative pressure atomization impregnation process with a mass ratio of acid-resistant inorganic modifying liquid to fused silica powder of 0.2:1. Under conditions of 20℃, negative pressure -0.03MPa, and atomization spray rate of 5mL / min, continuous closed atomization impregnation was performed for 20min to ensure uniform wetting of the fused silica powder surface by the acid-resistant inorganic modifying liquid, resulting in uniformly coated modified powder. The modified powder was then placed in a hot air drying oven and dried at 80℃ for 1.5h. The dried powder was placed in a high-temperature kiln and heated to 1150℃ at a rate of 4℃ / min, and calcined at a constant temperature for 2 hours. Then it was slowly cooled to 500℃ at a rate of 2℃ / min and allowed to cool naturally to room temperature. The cooled powder was then pulverized and passed through a 200-mesh standard sieve to obtain modified fused silica powder. The acid-resistant inorganic modification solution consisted of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 10:0.3:100. The crystal phase stabilizer consisted of yttrium oxide and cerium oxide in a mass ratio of 5:1.

[0071] The preparation method of the nano-silica functional sol includes the following preparation steps: The mass ratio of tetraethyl orthosilicate, anhydrous ethanol, and alkaline catalyst was controlled at 1:2.5:0.6. First, tetraethyl orthosilicate and anhydrous ethanol were mixed and stirred at room temperature and 200 rpm for 10 min until the system was completely homogeneous. Then, the alkaline catalyst was added dropwise to the system at a uniform rate over 30 min. After the addition was complete, the system temperature was controlled at 45℃ and the stirring speed at 200 rpm, and the hydrolysis reaction was carried out at this constant temperature for 3 h to obtain nano-silica sol. The mass ratio of nano-silica sol to bifunctional organosilane coupling agent was controlled at 100:4. The resulting nano-silica... A bifunctional organosilane coupling agent was added dropwise to the sol at a uniform rate for 40 minutes. After the addition was complete, the system temperature was maintained at 45°C and the stirring speed at 200 rpm for 3 hours. After the reaction was completed, the mixture was naturally cooled to room temperature and filtered through a 200-mesh filter cloth to remove impurities, yielding a nano-silica functional sol. The alkaline catalyst consisted of ammonia, anhydrous ethanol, and deionized water in a mass ratio of 12:25:50, with an ammonia concentration of 25%. The bifunctional organosilane coupling agent consisted of tridecafluorooctyltriethoxysilane and methacryloxypropyltrimethoxysilane in a mass ratio of 8:3.

[0072] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 15 minutes at a stirring speed of 800 rpm until the mixture is uniform to obtain a dry powder mixture. (2) Add hydrophobic additives and nano silica functional sol to the dry powder mixture, and continue mixing and stirring at room temperature for 10 minutes with a stirring speed of 800 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The pressing pressure is controlled at 25MPa and the pressure is held for 20s to obtain the brick blank. (4) The green bricks are dried in stages and gradients. First, they are pre-dried at 60℃ for 1 hour to remove free moisture from the surface of the bricks. Then, they are heated to 100℃ and dried at a constant temperature for 4 hours. After drying, they are sintered by gradient heating. The temperature is raised from room temperature to 600℃ at a rate of 8℃ / min and held for 1 hour. Then, the temperature is raised to 1280℃ at a rate of 8℃ / min and sintered at a constant temperature for 4 hours. After sintering, the temperature is lowered to 800℃ at a rate of 2℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, they are polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0073] Comparative Example 6 A high-strength, acid-resistant, and heat-resistant brick comprises the following raw materials in parts by weight: 40 parts modified fused silica powder, 20 parts high-alumina bauxite clinker, 10 parts calcined kaolin, 8 parts activated alumina powder, 5 parts zircon powder, 8 parts pyrophyllite, 5 parts nano-silica functional sol, and 0.5 parts hydrophobic additive; wherein the hydrophobic additive is stearic acid.

[0074] The method for preparing modified fused silica powder includes the following preparation steps: The fused silica powder was uniformly coated and modified using a negative pressure atomization impregnation process with a mass ratio of acid-resistant inorganic modifying liquid to fused silica powder of 0.2:1. Under conditions of 20℃, negative pressure -0.03MPa, and atomization spray rate of 5mL / min, continuous closed atomization impregnation was performed for 20min to ensure uniform wetting of the fused silica powder surface by the acid-resistant inorganic modifying liquid, resulting in uniformly coated modified powder. The modified powder was then placed in a hot air drying oven and dried at 80℃ for 1.5h. The dried powder was placed in a high-temperature kiln and heated to 1150℃ at a rate of 4℃ / min, and calcined at a constant temperature for 2 hours. Then it was slowly cooled to 500℃ at a rate of 2℃ / min and allowed to cool naturally to room temperature. The cooled powder was then pulverized and passed through a 200-mesh standard sieve to obtain modified fused silica powder. The acid-resistant inorganic modification solution consisted of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 10:0.3:100. The crystal phase stabilizer consisted of yttrium oxide and cerium oxide in a mass ratio of 5:1.

[0075] The preparation method of the nano-silica functional sol includes the following preparation steps: The mass ratio of tetraethyl orthosilicate, anhydrous ethanol, and alkaline catalyst was controlled at 1:2.5:0.6. First, tetraethyl orthosilicate and anhydrous ethanol were mixed and stirred at room temperature and 200 rpm for 10 min until the system was completely homogeneous. Then, the alkaline catalyst was added dropwise to the system at a uniform rate over 30 min. After the addition was complete, the system temperature was controlled at 45℃ and the stirring speed at 200 rpm, and the hydrolysis reaction was carried out at this constant temperature for 3 h to obtain nano-silica sol. The mass ratio of nano-silica sol to bifunctional organosilane coupling agent was controlled at 100:4. The resulting nano-silica... A bifunctional organosilane coupling agent was added dropwise to the sol at a uniform rate for 40 minutes. After the addition was complete, the system temperature was maintained at 45°C and the stirring speed at 200 rpm for 3 hours. After the reaction was completed, the mixture was naturally cooled to room temperature and filtered through a 200-mesh filter cloth to remove impurities, yielding a nano-silica functional sol. The alkaline catalyst consisted of ammonia, anhydrous ethanol, and deionized water in a mass ratio of 12:25:50, with an ammonia concentration of 25%. The bifunctional organosilane coupling agent consisted of tridecafluorooctyltriethoxysilane and methacryloxypropyltrimethoxysilane in a mass ratio of 8:3.

[0076] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 15 minutes at a stirring speed of 800 rpm until the mixture is uniform to obtain a dry powder mixture. (2) Add hydrophobic additives and nano silica functional sol to the dry powder mixture, and continue mixing and stirring at room temperature for 10 minutes with a stirring speed of 800 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The pressing pressure is controlled at 25MPa and the pressure is held for 20s to obtain the brick blank. (4) The green bricks are subjected to a segmented gradient drying process. First, they are pre-dried at 60℃ for 1 hour to remove free moisture from the surface of the bricks. Then, they are heated to 100℃ and dried at a constant temperature for 4 hours. After drying, they are subjected to gradient heating sintering. The temperature is raised from room temperature to 600℃ at a rate of 1℃ / min and held for 1 hour. Then, the temperature is raised to 1280℃ at a rate of 1℃ / min and sintered at a constant temperature for 4 hours. After sintering, the temperature is lowered to 800℃ at a rate of 2℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, they are polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0077] Comparative Example 7 A high-strength, acid-resistant, and heat-resistant brick comprises the following raw materials in parts by weight: 40 parts modified fused silica powder, 20 parts high-alumina bauxite clinker, 10 parts calcined kaolin, 8 parts activated alumina powder, 5 parts zircon powder, 8 parts pyrophyllite, 5 parts nano-silica functional sol, and 0.5 parts hydrophobic additive; wherein the hydrophobic additive is stearic acid.

[0078] The method for preparing modified fused silica powder includes the following preparation steps: The fused silica powder was uniformly coated and modified using an atmospheric pressure impregnation process with a mass ratio of acid-resistant inorganic modifying liquid to fused silica powder of 0.2:1. The powder was impregnated at 20℃ and atmospheric pressure for 20 minutes to ensure uniform wetting of the fused silica powder surface with the acid-resistant inorganic modifying liquid, resulting in uniformly coated modified powder. The modified powder was then placed in a hot air drying oven and dried at 80℃ for 1.5 hours. Finally, the dried powder was placed in a high-temperature kiln at 4℃ / m³. The temperature was gradually increased to 1150℃ at a rate of 10°C / min and calcined at a constant temperature for 2 hours. Then, it was slowly cooled to 500℃ at a rate of 2℃ / min and allowed to cool naturally to room temperature. The cooled powder was then pulverized and passed through a 200-mesh standard sieve to obtain modified fused silica powder. The acid-resistant inorganic modification solution consisted of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 10:0.3:100. The crystal phase stabilizer consisted of yttrium oxide and cerium oxide in a mass ratio of 5:1.

[0079] The preparation method of the nano-silica functional sol includes the following preparation steps: The mass ratio of tetraethyl orthosilicate, anhydrous ethanol, and alkaline catalyst was controlled at 1:2.5:0.6. First, tetraethyl orthosilicate and anhydrous ethanol were mixed and stirred at room temperature and 200 rpm for 10 min until the system was completely homogeneous. Then, the alkaline catalyst was added dropwise to the system at a uniform rate over 30 min. After the addition was complete, the system temperature was controlled at 45℃ and the stirring speed at 200 rpm, and the hydrolysis reaction was carried out at this constant temperature for 3 h to obtain nano-silica sol. The mass ratio of nano-silica sol to bifunctional organosilane coupling agent was controlled at 100:4. The resulting nano-silica... A bifunctional organosilane coupling agent was added dropwise to the sol at a uniform rate for 40 minutes. After the addition was complete, the system temperature was maintained at 45°C and the stirring speed at 200 rpm for 3 hours. After the reaction was completed, the mixture was naturally cooled to room temperature and filtered through a 200-mesh filter cloth to remove impurities, yielding a nano-silica functional sol. The alkaline catalyst consisted of ammonia, anhydrous ethanol, and deionized water in a mass ratio of 12:25:50, with an ammonia concentration of 25%. The bifunctional organosilane coupling agent consisted of tridecafluorooctyltriethoxysilane and methacryloxypropyltrimethoxysilane in a mass ratio of 8:3.

[0080] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 15 minutes at a stirring speed of 800 rpm until the mixture is uniform to obtain a dry powder mixture. (2) Add hydrophobic additives and nano silica functional sol to the dry powder mixture, and continue mixing and stirring at room temperature for 10 minutes with a stirring speed of 800 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The pressing pressure is controlled at 25MPa and the pressure is held for 20s to obtain the brick blank. (4) The green bricks are dried in sections and gradients. First, they are pre-dried at 60℃ for 1 hour to remove free moisture from the surface of the bricks. Then, they are heated to 100℃ and dried at a constant temperature for 4 hours. After drying, they are sintered by gradient heating. The temperature is raised from room temperature to 600℃ at a rate of 3℃ / min and held for 1 hour. Then, the temperature is raised to 1280℃ at a rate of 5℃ / min and sintered at a constant temperature for 4 hours. After sintering, the temperature is lowered to 800℃ at a rate of 2℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, they are polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0081] Comparative Example 8 A high-strength, acid-resistant, and heat-resistant brick comprises the following raw materials in parts by weight: 40 parts modified fused silica powder, 20 parts high-alumina bauxite clinker, 10 parts calcined kaolin, 8 parts activated alumina powder, 5 parts zircon powder, 8 parts pyrophyllite, 5 parts commercially available nano silica sol, and 0.5 parts hydrophobic additive; wherein the hydrophobic additive is stearic acid.

[0082] The method for preparing modified fused silica powder includes the following preparation steps: The fused silica powder was uniformly coated and modified using a negative pressure atomization impregnation process with a mass ratio of acid-resistant inorganic modifying liquid to fused silica powder of 0.2:1. Under conditions of 20℃, negative pressure -0.03MPa, and atomization spray rate of 5mL / min, continuous closed atomization impregnation was performed for 20min to ensure uniform wetting of the fused silica powder surface by the acid-resistant inorganic modifying liquid, resulting in uniformly coated modified powder. The modified powder was then placed in a hot air drying oven and dried at 80℃ for 1.5h. The dried powder was placed in a high-temperature kiln and heated to 1150℃ at a rate of 4℃ / min, and calcined at a constant temperature for 2 hours. Then it was slowly cooled to 500℃ at a rate of 2℃ / min and allowed to cool naturally to room temperature. The cooled powder was then pulverized and passed through a 200-mesh standard sieve to obtain modified fused silica powder. The acid-resistant inorganic modification solution consisted of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 10:0.3:100. The crystal phase stabilizer consisted of yttrium oxide and cerium oxide in a mass ratio of 5:1.

[0083] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 15 minutes at a stirring speed of 800 rpm until the mixture is uniform to obtain a dry powder mixture. (2) Add hydrophobic additives and commercially available nano silica sol to the dry powder mixture, and continue mixing and stirring at room temperature for 10 minutes with a stirring speed of 800 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The pressing pressure is controlled at 25MPa and the pressure is held for 20s to obtain the brick blank. (4) The green bricks are dried in sections and gradients. First, they are pre-dried at 60℃ for 1 hour to remove free moisture from the surface of the bricks. Then, they are heated to 100℃ and dried at a constant temperature for 4 hours. After drying, they are sintered by gradient heating. The temperature is raised from room temperature to 600℃ at a rate of 3℃ / min and held for 1 hour. Then, the temperature is raised to 1280℃ at a rate of 5℃ / min and sintered at a constant temperature for 4 hours. After sintering, the temperature is lowered to 800℃ at a rate of 2℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, they are polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0084] Comparative Example 9 A high-strength acid-resistant and heat-resistant brick comprises the following raw materials in parts by weight: 40 parts modified fused silica powder, 20 parts high-alumina bauxite clinker, 10 parts calcined kaolin, 8 parts activated alumina powder, 5 parts zircon powder, 8 parts pyrophyllite, and 0.5 parts hydrophobic additive; wherein the hydrophobic additive is stearic acid.

[0085] The method for preparing modified fused silica powder includes the following preparation steps: The fused silica powder was uniformly coated and modified using a negative pressure atomization impregnation process with a mass ratio of acid-resistant inorganic modifying liquid to fused silica powder of 0.2:1. Under conditions of 20℃, negative pressure -0.03MPa, and atomization spray rate of 5mL / min, continuous closed atomization impregnation was performed for 20min to ensure uniform wetting of the fused silica powder surface by the acid-resistant inorganic modifying liquid, resulting in uniformly coated modified powder. The modified powder was then placed in a hot air drying oven and dried at 80℃ for 1.5h. The dried powder was placed in a high-temperature kiln and heated to 1150℃ at a rate of 4℃ / min, and calcined at a constant temperature for 2 hours. Then it was slowly cooled to 500℃ at a rate of 2℃ / min and allowed to cool naturally to room temperature. The cooled powder was then pulverized and passed through a 200-mesh standard sieve to obtain modified fused silica powder. The acid-resistant inorganic modification solution consisted of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 10:0.3:100. The crystal phase stabilizer consisted of yttrium oxide and cerium oxide in a mass ratio of 5:1.

[0086] A method for preparing a high-strength, acid-resistant, and heat-resistant brick includes the following preparation steps: (1) Add modified fused silica powder, high alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, and dry mix at room temperature for 15 minutes at a stirring speed of 800 rpm until the mixture is uniform to obtain a dry powder mixture. (2) Add hydrophobic additive to the dry powder mixture, and continue mixing at room temperature for 10 minutes with a stirring speed of 800 rpm to obtain dry blank; (3) The dry blank is loaded into the mold and pressed into shape using isostatic pressing process. The pressing pressure is controlled at 25MPa and the pressure is held for 20s to obtain the brick blank. (4) The green bricks are dried in sections and gradients. First, they are pre-dried at 60℃ for 1 hour to remove free moisture from the surface of the bricks. Then, they are heated to 100℃ and dried at a constant temperature for 4 hours. After drying, they are sintered by gradient heating. The temperature is raised from room temperature to 600℃ at a rate of 3℃ / min and held for 1 hour. Then, the temperature is raised to 1280℃ at a rate of 5℃ / min and sintered at a constant temperature for 4 hours. After sintering, the temperature is lowered to 800℃ at a rate of 2℃ / min and cooled to room temperature with the furnace. After being taken out of the furnace, they are polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

[0087] Performance testing The high-strength acid-resistant and heat-resistant brick samples prepared in Examples 1-3 and Comparative Examples 1-9 of this application were subjected to various physicochemical property tests. All basic acid resistance, heat resistance, and mechanical property tests were conducted in accordance with the national standard GB / T 8488-2008 "Acid-resistant Bricks" and the industry standard JC / T 424-2005 "Acid-resistant and Heat-resistant Bricks". The specific test items, test conditions, and operating procedures are as follows: Room temperature compressive strength: Tested in accordance with industry standard JC / T 424-2005 "Acid-resistant and heat-resistant bricks"; Flexural strength at room temperature: Referring to industry standard JC / T 424-2005 "Acid-resistant and heat-resistant bricks", the flexural strength at room temperature of the samples was tested using the three-point bending method; Acid resistance: Referring to the national standard GB / T 8488-2008 "Acid-resistant bricks", the sample was immersed in a mixed acid solution at 90℃. The mixed acid solution was prepared by mixing equal volumes of sulfuric acid, hydrochloric acid, and nitric acid, each at 10% by weight. After immersion for 5 hours, the sample was removed, cleaned, dried, and weighed. The mass loss rate was calculated using the following formula: Mass loss rate (%) = [(initial mass - mass after corrosion) / initial mass] × 100%. The lower the mass loss rate, the better the acid resistance. Temperature resistance: Referring to industry standard JC / T 424-2005 "Acid and heat resistant bricks", cyclic thermal shock tests were conducted under three conditions of 200℃, 250℃, and 300℃ according to the standard's specified temperature difference gradient. The operating procedure is standardized: place the sample in a muffle furnace and heat it at a uniform rate to the high temperature range of the test and hold it at that temperature for 15 minutes; quickly remove the sample and immerse it in 25°C room temperature circulating cooling water to complete the rapid cooling, and complete the process in one cycle; Five consecutive cyclic impact tests were conducted under temperature differences of 200℃, 250℃, and 300℃, respectively, and defects such as cracks, chipping, peeling, and splitting were recorded. The evaluation criteria was that no visible cracks or damage were observed after five consecutive thermal cycles under the same temperature difference, which was considered as passing the test. Pressure resistance: Referring to the industry standard JC / T 424-2005 "Acid and heat resistant bricks", the sample was continuously subjected to 4MPa and held for 24h. After the pressure holding was completed, the compressive strength of the sample at room temperature was retested. At the same time, the sample was observed to see if there were micro-cracks, delamination, or breakage. If there were no appearance defects and the compressive strength decay rate was <3% after 24h of 4MPa pressure holding, the high pressure resistance stability was judged to be excellent and suitable for long-term use under high pressure corrosion conditions. Thermal conductivity: Tested according to national standard GB / T 10297-2015 "Determination of thermal conductivity of non-metallic solid materials - hot wire method"; The test results are shown in Table 1.

[0088] Table 1. Performance parameters of the high-strength acid-resistant and heat-resistant bricks prepared in Examples 1-3 and Comparative Examples 1-9. As shown in Table 1, the high-strength acid-resistant and heat-resistant bricks prepared in Examples 1-3 of this application exhibit excellent comprehensive performance. This application effectively improves the structural stability of the bricks by combining composite rare earth crystal phase stabilizers, synergistically cooperating with bifunctional silane-modified sols, and optimizing powder modification and sintering processes. The prepared bricks possess excellent mechanical strength, acid corrosion resistance, and high and low temperature thermal shock resistance. They also exhibit low high-pressure resistance decay rate and low thermal conductivity, solving the defects of traditional acid-resistant bricks such as poor thermal stability, easy cracking, weak corrosion resistance, and rapid decay of high-pressure performance. They can be adapted to harsh high-temperature, strong corrosion, and high-pressure working conditions for a long time.

[0089] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A high-strength, acid-resistant, and heat-resistant brick, characterized in that, The raw materials include the following parts by weight: 40-55 parts modified fused silica powder, 20-30 parts high-alumina bauxite clinker, 10-20 parts calcined kaolin, 8-15 parts activated alumina powder, 5-8 parts zircon powder, 8-10 parts pyrophyllite, 5-8 parts nano-silica functional sol, and 0.5-1.5 parts hydrophobic additives.

2. The high-strength acid-resistant and heat-resistant brick according to claim 1, characterized in that, The method for preparing the modified fused silica powder includes the following preparation steps: The modified powder was obtained by coating molten quartz powder with an acid-resistant inorganic modification liquid using a negative pressure atomization impregnation process. The modified powder is dried at low temperature, calcined at high temperature, pulverized and sieved to obtain modified fused silica powder.

3. The high-strength acid-resistant and heat-resistant brick according to claim 2, characterized in that, The acid-resistant inorganic modified liquid is composed of zirconium tetrachloride, a crystal phase stabilizer, and anhydrous ethanol in a mass ratio of 10-12:0.3-0.8:100; the crystal phase stabilizer is composed of yttrium oxide and cerium oxide in a mass ratio of 5-8:1-2.

4. The high-strength acid-resistant and heat-resistant brick according to claim 2, characterized in that, In the negative pressure atomization impregnation process, the negative pressure is -0.03MPa to -0.05MPa, and the atomization spray rate is 5-8mL / min; the low-temperature drying temperature is 80-100℃, and the drying time is 1.5-2.5h; the high-temperature calcination specifically involves: gradually increasing the temperature to 1150-1250℃ at a heating rate of 4-6℃ / min, calcining for 2-3h, and then slowly cooling to 500℃ at a cooling rate of 2-3℃ / min, followed by natural cooling to room temperature.

5. The high-strength acid-resistant and heat-resistant brick according to claim 1, characterized in that, The preparation method of the nano-silica functional sol includes the following preparation steps: Tetraethyl orthosilicate and anhydrous ethanol were mixed and stirred evenly. An alkaline catalyst was added dropwise, and the hydrolysis reaction was carried out at a constant temperature for 3-5 hours to obtain nano-silica sol. A bifunctional organosilane coupling agent was added dropwise to the nano-silica sol, and the mixture was stirred at a constant temperature for 3-5 hours. After cooling, the mixture was filtered to remove impurities to obtain nano-silica functional sol.

6. The high-strength acid-resistant and heat-resistant brick according to claim 5, characterized in that, The bifunctional organosilane coupling agent is composed of tridecafluorooctyltriethoxysilane and methacryloxypropyltrimethoxysilane in a mass ratio of 8-12:3-5.

7. The high-strength acid-resistant and heat-resistant brick according to claim 1, characterized in that, The hydrophobic additive is stearic acid and / or polyethylene wax.

8. A method for preparing high-strength acid-resistant and heat-resistant bricks as described in any one of claims 1-7, characterized in that, The preparation steps include the following: (1) Add modified fused silica powder, high-alumina bauxite clinker, calcined kaolin, activated alumina powder, zircon powder and pyrophyllite into a high-speed dry powder mixer, dry mix for 15-25 minutes, mix evenly to obtain dry powder mixture. (2) Add hydrophobic additives and nano-silica functional sol to the dry powder mixture, and continue mixing and stirring for 10-15 minutes to obtain dry blanks; (3) The dry blank is pressed into shape using isostatic pressing to obtain the brick green blank; (4) The green bricks are sequentially dried in sections and sintered in gradient heating. After sintering, the temperature is lowered and cooled with the furnace. After being taken out of the furnace, they are polished, sorted and inspected to obtain high-strength acid-resistant and heat-resistant bricks.

9. The method for preparing high-strength acid-resistant and heat-resistant bricks according to claim 8, characterized in that, In step (3), the static pressure molding pressure is 25-35 MPa, and the holding time is 20-30 s.

10. The method for preparing high-strength acid-resistant and heat-resistant bricks according to claim 8, characterized in that, The segmented gradient drying in step (4) specifically involves: first pre-drying at 60-70℃ for 1-2 hours, then raising the temperature to 100-120℃ and drying at a constant temperature for 4-6 hours; the gradient heating sintering specifically involves: raising the temperature from room temperature to 600-650℃ at a heating rate of 3-5℃ / min, holding at that temperature for 1-2 hours, then raising the temperature to 1280-1350℃ at a heating rate of 5-8℃ / min, and sintering at a constant temperature for 4-6 hours.